Efficacy and safety of high-power short duration atrial fibrillation ablation in elderly patients - Müller, Julian; Nentwich, Karin; Berkovitz, Artur; Ene, Elena; Sonne, Kai; Chakarov, Ivaylo; Barth, Sebastian; Waechter, Christian; Lüsebrink, Ulrich; Behnes, Michael; Akın, Ibrahim; Deneke, Thomas (Journal of cardiovascular electrophysiology, 2022)
Introduction Data about atrial fibrillation (AF) ablation using high-power short duration (HPSD) radiofrequency ablation in the elderly population is still scarce. The aim of our study was to investigate the efficacy and safety of HPSD ablation in patients over 75 years compared to younger patients. Methods Consecutive patients older than 75 years with paroxysmal or persistent AF undergoing a first-time AF ablation using 50 W HPSD ablation approach were analyzed in this retrospective observational analysis and compared to a control group <75 years. Short-term endpoints included intraprocedural reconnection of at least one pulmonary vein (PV) and intrahospital and AF recurrence during 3 months blanking period, as well as a long-term endpoint of freedom from atrial arrhythmias of antiarrhythmic drugs after 12 months. Results A total of 540 patients underwent a first AF ablation with HPSD (66 ± 10 years; 58% male; 47% paroxysmal AF). Mean age was 78 ± 2.4 and 63 ± 6.3 years (p < .001), respectively. Elderly patients were significantly more often women (p < .001). The procedure, fluoroscopy, and ablation were comparable. Elderly patients revealed significantly more often extra-PV low-voltage areas requiring additional left atrial ablations (p < .001). Overall complication rates were low; however, elderly patients revealed higher major complication rates mainly due to unmasking sick sinus syndrome (p = .003). Freedom from arrhythmia recurrences was comparable (68% vs. 76%, log-rank p = .087). Only in the subgroup of paroxysmal AF, AF recurrences were more common after 12 months (69% vs. 82%; log-rank p = .040; hazard ratio: 1.462, p = .044) in the elderly patients. In multivariable Cox regression analysis of the whole cohort persistent AF, female gender, diabetes mellitus and presence of left atrium low-voltage areas, but not age >75 years were associated with AF recurrences. Conclusion HPSD AF ablation of patients >75 years in experienced centers is safe and effective. Therefore, age alone should not be the reason to withhold AF ablation from vital elderly patients due to only a slightly worse outcome and safety profile. In paroxysmal AF, elderly patients have more recurrences compared to the younger control group.